Maternal hereditary hemolytic anemia and birth defects in the National Birth Defects Prevention Study. Issue 8 (5th March 2022) - Papadopoulos, Eleni A.; Fisher, Sarah C.; Howley, Meredith M.; Browne, Marilyn L.
Abstract: Objectives: Hereditary hemolytic anemia (HHA) results from genetic mutations that cause red blood cell abnormalities. Little research exists on the relationship between HHA and birth defects. Using data from the National Birth Defects Prevention Study (NBDPS), we described characteristics of HHA‐exposed women and estimated associations between HHA during pregnancy and specific birth defects. Methods: The NBDPS was a population‐based, case–control study of major birth defects and included pregnancies with estimated delivery dates from October 1997 through December 2011. Participants were ascertained from hospital discharge lists or birth defect registries at 10 sites. Trained interviewers collected information about pregnancy exposures via telephone questionnaire. We described characteristics among HHA‐exposed women and calculated crude odds ratios and exact 95% confidence intervals for defects with ≥3 exposed cases. Results: Among 31 HHA‐exposed women (28 cases/3 controls), 13 (42%) reported sickle cell anemia, 17 (55%) reported thalassemia, and one (3%) reported hereditary spherocytosis. The average age at delivery for HHA‐exposed case women was 27.3 years (range: 17–38). The majority (82%) of HHA‐exposed case women reported additional conditions during pregnancy, including hypertension, genitourinary infections, and respiratory illnesses. Additionally, 93% of case women reported using medication during pregnancy. Among the 28 cases, 18 (64%) had isolated birth defects. The defects with ≥3 exposed cases were anencephaly, atrial septal defect, gastroschisis, and cleft palate. Except for anencephaly, the 95% confidence intervals for all estimates were close to or included the null. Conclusion: This hypothesis‐generating study adds to the sparse literature on the association between HHA and birth defects.